Influence of Neutral Currents on Electron and Gamma Polarizations in the Process e+N→e′+N+γ - N. V. Samsonenko; Adamou Ousmane Manga; Almoustapha Aboubacar; Aboubacar Moussa (Advances in High Energy Physics)
The differential cross section of electron inelastic scattering by nuclei followed by γ radiation is calculated using the multipole decomposition of the hadronic currents and by taking into account the longitudinal polarization of the initial electron and the circular polarization of the γ radiation. We performed the analysis of the angular and energy dependence of the degree of electron and photon polarization which can yield information on values of weak neutral currents parameters.